Profil Berpikir Kritis Siswa dalam Menyelesaikan Soal Fungsi Komposisi melalui Model Pembelajaran Kolaboratif - Icha Shofia Karlita Ulfa; Dinawati Trapsilasiwi; Erfan Yudianto (Universitas Syiah Kuala, 2018)
Critical thinking is one of the high-level thinking. Mathematics learning in globalization era usually uses critical thinking in solving problems. Mathematics is always thought as the difficult one to be learnt. This research will describe students critical thinking profile in solving the function of compositions through collaborative learning. This reseach can be used as the reference for teachers to recognize students critical thinking profile in their class, and also it can be used to motivate students to enhance their critical thinking ability. The critical thinking criterias are focus, reason, inference, situation, and overview. That criterias include eleven indicators. The type of collaborative learning in this research is Learning Together (LT). This research is descriptive with qualitative approach. The data were collected by documentation, observation, test, and interview. The subjects of this research are six students who are two high-achiever students, two medium-achiever students, and two low-achiever students from one of senior high school at Jember. High-achiever students can achieve all criterias of critical thinking and they dominate the role in learning and teaching activity. The medium-achiever students only fulfill focus in the first and second indicator, reason in the second, and inference, situation, clarity, and overview in the second indicator and also can join in the collaborative learning. While, the low-achiever students can only look to other students without get engaged actively in collaborative learning and only achieve focus in the first and second indicators of situation.